Family upbringing styles and school violence in adolescents from Lima Norte - Meza Gonzales, Angela Milagros (2021)
In order to determine the relationship between family parenting styles and levels of school violence, this study was carried out among adolescents between 12 and 18 years of age living in various districts of northern Lima, the sample consisted of 300 participants of both sexes. The study of applied type and under the non-experimental cross sectional design with descriptive - explanatory approach, is carried out using 2 instruments; the questionnaire of family parenting styles (ECF-29) Estrada et al. (2017) and the school violence scale of Emler and Reicher (1995) and adapted by Estévez et al. (2005). The results showed that there is significant association (p=.000) between family parenting styles and levels of school violence in adolescents. They showed greater school violence in the group with authoritarian and overprotective family upbringing. On the other hand, the authoritarian parenting style is directly related to school violence, as is the case with the indulgent style, but not with the democratic parenting style.